Diagnostic Value of Advanced Metal Artifact Reduction Magnetic Resonance Imaging for Periprosthetic Joint Infection. Issue 3 (19th May 2022) - Inaoka, Tsutomu; Kitamura, Noriko; Sugeta, Masayuki; Nakatsuka, Tomoya; Ishikawa, Rumiko; Kasuya, Shusuke; Sugiura, Yoshiya; Nakajima, Arata; Nakagawa, Koichi; Terada, Hitoshi
Purpose: This study aimed to evaluate the diagnostic value of magnetic resonance imaging with multiacquisition variable–resonance image combination selective for periprosthetic joint infection (PJI). Materials and Methods: Magnetic resonance imaging around metal joint prostheses including multiacquisition variable–resonance image combination selective at 1.5 T (from April 2014 to August 2020) was retrospectively evaluated by 2 radiologists for detection of abnormal findings (joint effusion, capsular thickening, pericapsular edema, soft-tissue fluid collection, soft-tissue edema, bone marrow edema pattern around the implant [BME pattern], lymphadenopathy, and others) and overall image impression for PJI. Regarding the soft-tissue fluid collection, presence of communication to the joint or capsular-like structure was evaluated. Clinical assessments were recorded. Positive predictive values (PPVs), negative predictive values (NPVs), and odds ratios (ORs) for PJI were calculated for the abnormal findings. Overall image impression for PJI was evaluated. χ 2, Fisher exact, t, and Mann-Whitney U tests and receiver operating characteristic analysis were used. Interobserver agreement was assessed with κ statistics. Results: Forty-three joints in 36 patients (mean ± SD age, 75.4 ± 8.8 years; 30 women; hip [n = 29], knee [n = 12], and elbow [n = 2]) were evaluated. Eighteen joints (42%) were clinically diagnosed as PJI. The findings suggesting PJI were capsular thickening (PPV, 70%; NPV, 90%; OR, 20.6), soft-tissue fluid collection (PPV, 81%; NPV, 81%; OR, 19.1), soft-tissue edema (PPV, 67%; NPV, 89%; OR, 17), pericapsular edema (PPV, 76%; NPV, 81%; OR, 13.7), and joint effusion (PPV, 55%; NPV, 100%; OR, 12). Soft-tissue fluid collection without capsular-like structure (PPV, 83%; NPV, 74%; OR, 14.4) or with communication to the joint (PPV, 75%; NPV, 71%; OR, 7.3) suggested PJI. The combinations of joint effusion, capsular thickening, pericapsular edema, soft-tissue fluid collection, and soft-tissue edema highly suggested PJI. Regarding the BME pattern, the combination with soft-tissue edema raised the possibility of PJI (PPV, 73%; NPV, 69%; OR, 5.9). Regarding the interobserver agreements for each abnormal finding, κ values were 0.60 to 0.77. Regarding the overall image impression, weighted κ value was 0.97 and areas under the receiver operating characteristic curve were 0.949 (95% confidence interval, 0.893–1.005) and 0.926 (95% confidence interval, 0.860–0.991) with no significant difference ( P = 0.534). Conclusions: The findings suggesting PJI were capsular thickening, soft-tissue fluid collection, soft-tissue edema, pericapsular edema, and joint effusion. The combinations of them highly suggested PJI. Regarding the BME pattern, the combination with soft-tissue edema raised the possibility of PJI.